2018
DOI: 10.1002/2017ef000720
|View full text |Cite
|
Sign up to set email alerts
|

Regional Climate Impacts of Stabilizing Global Warming at 1.5 K Using Solar Geoengineering

Abstract: The 2015 Paris Agreement aims to limit global warming to well below 2 K above preindustrial levels, and to pursue efforts to limit global warming to 1.5 K, in order to avert dangerous climate change. However, current greenhouse gas emissions targets are more compatible with scenarios exhibiting end‐of‐century global warming of 2.6–3.1 K, in clear contradiction to the 1.5 K target. In this study, we use a global climate model to investigate the climatic impacts of using solar geoengineering by stratospheric aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 104 publications
3
81
0
Order By: Relevance
“…Geoengineering has been proposed as a way to limit global warming by deliberately altering the climate to both alleviate some of the consequences of anthropogenic greenhouse gas emissions (Irvine et al, ) and as part of strategic approach to keep temperatures below thresholds such as 1.5 °C above pre‐industrial (Jones et al, ; MacMartin & Kravitz, ). Climate models simulating the Atlantic Meridional Over‐turning Circulation (AMOC) show that it decreases in intensity as atmospheric greenhouse gas concentrations and temperatures rise.…”
Section: Introductionmentioning
confidence: 99%
“…Geoengineering has been proposed as a way to limit global warming by deliberately altering the climate to both alleviate some of the consequences of anthropogenic greenhouse gas emissions (Irvine et al, ) and as part of strategic approach to keep temperatures below thresholds such as 1.5 °C above pre‐industrial (Jones et al, ; MacMartin & Kravitz, ). Climate models simulating the Atlantic Meridional Over‐turning Circulation (AMOC) show that it decreases in intensity as atmospheric greenhouse gas concentrations and temperatures rise.…”
Section: Introductionmentioning
confidence: 99%
“…Stratospheric aerosol geoengineering could be considered as part of a portfolio of options for managing future climate change (Crutzen, 2006;Keith & MacMartin, 2015;Long & Shepherd, 2014;MacMartin et al, 2018;Wigley, 2006) and could reduce many impacts relative to the warmer world without geoengineering (e.g., Keith & Irvine, 2016). However, while geoengineering could be used to maintain some particular target for global mean temperature, such as a 1.5 or 2 • C rise above preindustrial levels, the resulting climate would not be the same as one in which these targets were achieved solely through limiting atmospheric greenhouse gas (GHG) concentrations (e.g., Jones et al, 2018;MacMartin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Deploying it with a radiative forcing large enough to offset all temperature changes is simulated to, for example, weaken the global hydrological cycle, more-than-offsetting the strengthening expected under climate change (Govindasamy andCaldeira 2000, Tilmes et al 2013). However, modeling studies have found that if deployed to offset all warming it would nevertheless reduce many aspects of change to mean climate and climate extremes relative to a case without solar geoengineering (Boucher et al 2013, Kravitz et al 2013, Curry et al 2014, Jones et al 2018. In addition, there are sideeffects of stratospheric aerosol geoengineering such as ozone loss and air pollution that are expected to grow as the scale of deployment grows (Crutzen 2006, Eastham et al 2018.…”
Section: Introductionmentioning
confidence: 99%